PENERAPAN STRATEGI PEMBELAJARAN INKUIRI-STAD (INSTAD) UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS DAN HASIL BELAJAR BIOLOGI SISWA KELAS X MAN 2 MODEL PEKANBARU - Isliyandi, Abdul Isliyandi Abdul; Natalina L, Mariani Natalina L (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: A class action research has been done to increase science process skill andbiology student learn result of class X MIA 3 MAN 2 Model Pekanbaru by applying ofINSTAD learning strategy. This research was conducted from February to March 2015. Thesubjects of this research were the students of class X MIA 3 MAN 2 Model Pekanbaru,consists of 9 boys and 20 girls. The parameters on this were science process skill and studentlearn result. Before applying of INSTAD learning strategy, science process skill was 65.65%(C+). After applying of INSTAD learning strategy, science process skill increase into 84.43%(B+) at cycle I and 93.57% (A-) at cycle II. Student learn result consist of absorb ability was84.72% (B+) at cycle I and increase into 90.72% (A-) at cycle II, pass learn was 86.21 %(B+) at cycle I and increase into 96.56 % (A-) at cycle II, erudite attitude was 82.33 %(Good) at cycle I and increase into 89.12 % (Very Good) at cycle II, skill of product makingwas 92.96 % (A-) at cycle I and increase into 95.11 % (A-) at cycle II. From the result of thisresearch concluded that applying of INSTAD learning strategy can increase science processskill and biology learn result of student class X MIA 3 MAN 2 Model Pekanbaru.Key words : INSTAD learning strategy, science process skill, biology student learn result